Quantification of key developmental risks in Africa - Bakhtina, V.; Zgurovsky, M. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2008)
Current research identifies six key developmental risks for Africa: (a) vulnerability of infrastructure, (b) health, (c) education, (d) political and security risk, (e) vulnerability to natural disasters and (f) limitation of access to drinking water and sanitary facilities. Key risks are combined to an integrated risk measure and their impact on 42. African countries is analyzed. Six countries most susceptible to the indicated set of risks are isolated. Визначено шість основних ризиків сталого розвитку Африки: 1) інфраструктура, 2) охорона здоров’я, 3) освіта, 4) політика та держбезпека, 5) природні катаклізми, 6) обмежений доступ до питної води і санітарних засобів. Ці ризики об’єднано поняття єдиного інтегрального ризику. Проаналізовано їх вплив на розвиток 42 країн Африки. Виокремлено шість країн, найбільш вразливих до дії цього набору ризиків. Выделены шесть основных рисков устойчивого развития Африки: 1) инфраструктура, 2) здравоохранение, 3) образование, 4) политика и госбезопасность,
5) природные катаклизмы, 6) ограниченный доступ к питьевой воде и санитарным
средствам. Перечисленные риски объединены в понятие единого интегрального
риска. Проанализировано их влияние на развитие 42 стран Африки. Выделены
шесть стран, наиболее чувствительных к действию этого набора рисков.